HOTS assessment in circulatory system learning: Validity, reliability, and item quality - Yosi Laila Rahmi; Isnaini Nur Habibah; Z. Zulyusri; Rahmawati Darussyamsu (JPBI (Jurnal Pendidikan Biologi Indonesia), 2021)
Biology learning, based on the curriculum-2013, requires students to be skilled at analyzing, evaluating, and creating to achieve Higher-Order Thinking Skills (HOTS). Thus, HOTS assessment instrument is crucial to be made. This study aimed to produce HOTS assessment instrument focused on circulatory system materials for XI graders. This research was conducted by using Research and Development (R&D) method with 4-D model. The subjects of this study were: two biology lecturers from Faculty of Mathematics and Science of Universitas Negeri Padang, two biology teachers, and 33 XI graders of Public Senior High School 1 Nan Sabaris. The data were collected using questionnaires which were validated by experts and analyzed using ANATES 4.09. The validity results reached as high as 87.54% (very valid) in which the empirical validity value was 88%. Meanwhile, the instrument was stated as very reliable (0.78), has a moderate difficulty, good differentiating power, and excellent option quality. Thus, as the recommendation, this instrument can be used to foster students’ HOTS.